1997
DOI: 10.1007/978-1-4899-1792-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide-Mediated Polymerization of Whey Proteins in Whey Protein Isolate-Stabilized Emulsions

Abstract: The effects of protein polymerization in whey protein isolate-stabilized emulsions on emulsion properties were investigated. Polymerization, involving intermolecular disulfide bonds between whey proteins adsorbed at the oil-water interface, increased with increasing storage time following emulsion formation. Ageing resulted in increased aggregation of emulsion droplets, emulsion viscosity and susceptibility to creaming but these effects were lower when thiol-disulfide interchange reactions were inhibited by N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The conventional emulsion is likely to have a monolayer of adsorbed globular proteins formed during homogenization, whereas the nanoemulsion is likely to have a multilayer of adsorbed proteins. After adsorption, globular proteins tend to unfold and form covalent cross-links (disulfide bonds) with their nearest neighbors . Consequently, this cross-linked protein layer may become crinkled when the droplets in the nanoemulsions shrink during ethyl acetate removal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional emulsion is likely to have a monolayer of adsorbed globular proteins formed during homogenization, whereas the nanoemulsion is likely to have a multilayer of adsorbed proteins. After adsorption, globular proteins tend to unfold and form covalent cross-links (disulfide bonds) with their nearest neighbors . Consequently, this cross-linked protein layer may become crinkled when the droplets in the nanoemulsions shrink during ethyl acetate removal.…”
Section: Resultsmentioning
confidence: 99%
“…Visual observation of the nanoemulsions indicated that they remained fairly transparent at holding temperatures less than 70 °C but became increasingly turbid at higher temperatures (data not shown). The increase in droplet aggregation at high temperatures can be attributed to an increase in the surface hydrophobicity of the droplets due to protein unfolding, which leads to a strong hydrophobic attraction between the droplets , . The overall attractive force was then presumably strong enough to overcome the net repulsive force, such as steric and electrostatic forces.…”
Section: Resultsmentioning
confidence: 99%
“…Whey proteins contain a large amount of sulfur‐containing amino acids that form disulfide bonds, giving globular proteins their compact shape. These disulfide bonds are usually broken when proteins unfold at a surface (“surface denaturation”) or due to heating (“thermal denaturation”), and may be involved in intra‐ or intermolecular interactions with other sulfhydryl groups (Monahan and others ). The thermal denaturation temperature of β‐lactoglobulin and α‐lactalbumin are fairly similar being around 65 to 85 °C, with the precise value depending on pH, salt concentration, cosolvents, and measurement method (Peltonenshalaby and Mangino ; Boye and Alli ; Fitzsimons and others ).…”
Section: Emulsions: Formation Stability and Propertiesmentioning
confidence: 99%
“…Monahan et al. reported polymerization involving intermolecular disulfide bonds between adsorbed whey proteins takes place at the oil–water interface leading to an increased level of aggregation of emulsion droplets . Additionally, at protein concentrations above the critical limit, it is possible that unadsorbed proteins in the aqueous dispersion could undergo conformational changes at high UHPs causing association and consequent aggregates that can contribute to the light scattering during size analysis .…”
Section: Resultsmentioning
confidence: 99%